THE VALUE OF ECONOMICS FOR THE ACCOUNTANT. - Blodgett, Ralph H. (The Accounting Review, 1943)
Abstract The article focuses on the importance of the knowledge of general economics for an accountant. It is insisted in this article that students of accountancy should do more work in general economics, and in advanced economics courses which are not very directly related to the field of accountancy, than they now do. Many accountants argue that economic principles and theories depend upon a great number of assumed conditions, many of which exist most imperfectly, in actual economic life, these principles and theories therefore seem to apply to some other world than this one and seem to have little significance for practical men who must concern themselves with economic life as it actually exists. According to the author this attitude toward economic theory, probably results from inadequate teaching in theory courses, poor textbooks, or some deficiency on the part of the students themselves. Economic theory is, of course, interested in the general aspects of economic phenomena and their typical relationships, properly and necessarily abstract and deductive.